Vocational Students' Perceptions of Mobile Assisted Language Learning (MALL) Materials - Helena Octavia; Utami Widiati; Enny Irawati (Pascasarjana Universitas Negeri Malang, 2019)
Abstract:  Digital resources have been proven able to assist English language learners in improving their interaction skills, widening their vocabulary range, and enhancing their reading comprehension. Despite their benefits, digital tools can also create distractions for students. This article reports on the result of a survey to 150 vocational students on Mobile Assisted Language Learning (MALL) materials. The students agreed that MALL materials were more authentic (67%) and more accessible (59%) than traditional learning materials. The use of MALL materials could trigger classroom interactions (64%) and facilitated learning (56%). The implementation of MALL materials allowed students to get immediate feedback from the teachers (73%). Abstrak: Sumber daya digital telah terbukti dapat membantu pelajar bahasa Inggris dalam meningkatkan keterampilan interaksi, memperluas jangkauan kosa kata, dan meningkatkan pemahaman bacaan mereka. Selain bermanfaat, alat digital juga dapat menggangu proses belajar. Artikel ini melaporkan hasil survei terhadap 150 siswa kejuruan terkait dengan implementasi materi berbasis gawai atau Mobile Assisted Language Learning (MALL). Ditemukan bahwa siswa sepakat bahwa materi MALL lebih otentik (67%) dan lebih mudah diakses (59%) daripada materi pembelajaran tradisional. Penggunaan MALL dapat memicu interaksi kelas (64%) dan memfasilitasi pembelajaran (56%). Dengan menerapkan materi berbasis gawai atau MALL materials di kelas, para siswa mengakui bahwa mereka bisa mendapatkan umpan balik langsung dari para guru (73%).